NEW APPROACHING OF Thx DSrU1.7 NANO-MATERIALS ON ABRIKOSOV-BALSEIRO-RUSSELL (ABR) MODEL AT 485 TESLA GYRO-ACCELERATOR FOR ENVIRONMENTALLY FRIENDLY REACTOR TECHNOLOGY - Hardiyanto, Moh. (Jurnal Teknologi, 2018)
Our research present a source of correlated photon pairs in Abrikosov-Balseiro-Russell (ABR) formalism that relies on spontaneous scattering in Thx DSrUO nano structure. Quantum correlations are shown between photon pairs that are generated through four-photon scattering where the pump photons are degenerate at a wavelength of 822.78 nm with 2.63 x 105 currie/mm fast thermal neutron floating, and the signal also idler photons are non degenerated at wavelength of 766.45 nm and 769.53 nm, respectively. In non-Abellian system for ABR formalism, the quantum approaching will be shown Cerenkov’s effect existing, then the Betha Group Large Hadron Collider (LHC) CERN, France nuclear reactor using by Thx DSrU1.7 nano materials matrix to be barrier for 2.63 x 105 currie/mm fast thermal neutron floating before the anti-neutrino particle shown up at 485 tesla particullary. Careful adjustment of the pump wavelength and polarization in Dirac’s condition are shown to be critical to observing quantum correlations on gyro-accelerator for environmentally friendly reactor technology.